Impact of tapering and discontinuation of bevacizumab in patients with progressive glioblastoma - Berberich, Anne; Hielscher, Thomas; Menn, Oliver Josef; Wiestler, Benedikt; Winkler, Frank; Platten, Michael; Wick, Wolfgang; Wick, Antje (Journal of neuro-oncology, 2016)
Bevacizumab is frequently used in patients with progressive glioblastoma raising questions regarding frequency of treatments, dosage, duration of therapy and the possibility of tapering and discontinuation for selected patient groups. We retrospectively assessed the safety and outcome of tapering and discontinuation of bevacizumab therapy for reasons other than disease progression and toxicity in 19 patients with progressive glioblastoma receiving bevacizumab for at least 6 months. In 10 of the 19 patients tapering bevacizumab resulted in complete discontinuation and reinitiation after disease progression during halted treatment. As a comparison group 33 patients with bevacizumab for at least 6 months continuously dosed at 10 mg/kg every 2 weeks were selected. Age and Karnofsky performance status at start of bevacizumab were similar in both groups. Influenced by the selection process, progression-free survival (PFS) and overall survival (OS) were longer in the group receiving a tapered and discontinued bevacizumab regimen (PFS 22.7 versus 11.2 months, HR 0.33, p-value = 0.01; OS 29.9 versus 15.5 months, HR 0.22, p-value = 0.001) with a median time of discontinuation of 4.5 months (range: 1.9-44.2 months). Stable disease or partial response according to RANO at ≥3 months was achieved in 89 % of patients with reinitiated bevacizumab therapy after discontinuation. These data indicate that tapering and discontinuation of bevacizumab therapy for other reasons than progression is feasible without an increased risk for tumor rebound or unresponsiveness to reinitiated bevacizumab therapy.